2021
DOI: 10.1371/journal.pone.0250571
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bacterial and archaeal communities in two fertilizer doses and soil compartments under continuous cultivation system of garlic

Abstract: Soil microbial communities are affected by interactions between agricultural management (e.g., fertilizer) and soil compartment, but few studies have considered combinations of these factors. We compared the microbial abundance, diversity and community structure in two fertilizer dose (high vs. low NPK) and soil compartment (rhizosphere vs. bulk soils) under 6-year fertilization regimes in a continuous garlic cropping system in China. The soil contents of NO3– and available K were significantly higher in bulk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 57 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Other studies have indicated that continuous cultivation of different agricultural plants has diferent efects on bacterial communities in diferent soil complexes (e.g., the rhizosphere soil and bulk soil) [35][36][37]. In addition, long-term use of high doses of nitrogen, phosphorus, and potassium (NPK) fertilizers reduces the richness of soil bacterial species [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have indicated that continuous cultivation of different agricultural plants has diferent efects on bacterial communities in diferent soil complexes (e.g., the rhizosphere soil and bulk soil) [35][36][37]. In addition, long-term use of high doses of nitrogen, phosphorus, and potassium (NPK) fertilizers reduces the richness of soil bacterial species [38,39].…”
Section: Introductionmentioning
confidence: 99%